2008
DOI: 10.1177/1352458507086425
|View full text |Cite
|
Sign up to set email alerts
|

Herpesviruses and human endogenous retroviral sequences in the cerebrospinal fluid of multiple sclerosis patients

Abstract: The findings described here show that HHV infection is more frequent in the CSF of MS patients than in patients with other neurological diseases; however, only HHV-6 seems to be involved in the pathogenesis of MS in a subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 64 publications
2
57
0
5
Order By: Relevance
“…Such a reactivation has been reported by Serafini et al, who detected an increased EBV reactivation in post-mortem brain tissue of two acute MS cases [18]. However, EBV-infected B cells [35] and EBV cell-free virions [18,36] were rarely observed in the CSF of MS patients. This may be accounted for by the low frequency of B cells present in the CSF [37], the maintenance of virus-specific memory CD8 1 T cells in the absence of cognate antigen [38] or by the specific presence of reservoirs for EBV in other brain compartments [18].…”
Section: Discussionsupporting
confidence: 54%
“…Such a reactivation has been reported by Serafini et al, who detected an increased EBV reactivation in post-mortem brain tissue of two acute MS cases [18]. However, EBV-infected B cells [35] and EBV cell-free virions [18,36] were rarely observed in the CSF of MS patients. This may be accounted for by the low frequency of B cells present in the CSF [37], the maintenance of virus-specific memory CD8 1 T cells in the absence of cognate antigen [38] or by the specific presence of reservoirs for EBV in other brain compartments [18].…”
Section: Discussionsupporting
confidence: 54%
“…Only the results of the following studies were positive: AlvarezLafuente et al [21], Mancuso et al [32] and Sanders et al [39]. The Sanders et al [39] study also showed the percentage of positive results as being greater in controls than in cases.…”
Section: Detection Of Ebv Dna In Brain Tissue and In Csfmentioning
confidence: 96%
“…Studies that detected EBV DNA in brain tissue [30,39] and CSF [21,26,30,32,33] (Table 7) failed to prove the association between the virus and the disease. Only the results of the following studies were positive: AlvarezLafuente et al [21], Mancuso et al [32] and Sanders et al [39].…”
Section: Detection Of Ebv Dna In Brain Tissue and In Csfmentioning
confidence: 99%
“…Two studies achieved statistically significant results between MS patients and controls and were classified as A quality. 28,53 Liedtke et al 28 studied both cellular and acellular samples. Another 2 studies were classified as A quality.…”
Section: Polymerase Chain Reaction Techniquesmentioning
confidence: 99%